The role of mesenchymal stem cell transplantation for ischemic stroke and recent research developments - Zhou, Li; Wang, Jiani; Huang, Jiagui; Song, Xiaosong; Wu, Youlin; Chen, Xia; Tan, Yongjun; Yang, Qin (Frontiers in Neurology, 2022)
Ischemic stroke is a common cerebrovascular disease that seriously affects human health. However, most patients do not practice self-care and cannot rely on the current clinical treatment for guaranteed functional recovery. Stem cell transplantation is an emerging treatment studied in various central nervous system diseases. More importantly, animal studies show that transplantation of mesenchymal stem cells (MSCs) can alleviate neurological deficits and bring hope to patients suffering from ischemic stroke. This paper reviews the biological characteristics of MSCs and discusses the mechanism and progression of MSC transplantation to provide new therapeutic directions for ischemic stroke.